1972
DOI: 10.1507/endocrj1954.19.203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ACTH <I>in vivo</I> on the Phospholipid Exchange between Adrenal Microsomes and Mitochondria <I>in vitro</I>

Abstract: Effect of ACTH administration on the rate of phospholipid exchange in vitro between rat adrenal microsomes and mitochondria was examined using 3H-cholinelabeled adrenal microsomes as the donor of phospholipids. Increased rate of exchange was observed between control microsomes and mitochondria isolated from rats received 6 u. of ACTH 3.5 hr before death of the animals. On the contrary, mitochondria obtained from the animals treated with ACTH for consecutive 3 days exhibited less capacity of the exchange. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
1977
1977

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The ammonium sulphate fraction was then desalted by passage through a Sephadex G25 column (30 x 2 cm) equilibrated with 50 mM sodium glycerophosphate buffer pH 6.5, 1 mM MgC12, 4 mM sodium fluoride and 2 mM theophylline and the protein fractions were pooled. This procedure removed endogenous nucleotides and gave the optimal conditions for protein kinase activity [31].…”
Section: Preincubation Of the Ammonium Sulphate Fraction With [~-~' Pmentioning
confidence: 99%
“…The ammonium sulphate fraction was then desalted by passage through a Sephadex G25 column (30 x 2 cm) equilibrated with 50 mM sodium glycerophosphate buffer pH 6.5, 1 mM MgC12, 4 mM sodium fluoride and 2 mM theophylline and the protein fractions were pooled. This procedure removed endogenous nucleotides and gave the optimal conditions for protein kinase activity [31].…”
Section: Preincubation Of the Ammonium Sulphate Fraction With [~-~' Pmentioning
confidence: 99%
“…The cyclic AMP assay of Brown et al (1971) has been reported to be useful also when bound and free radioactivity is separated with membrane filters (Tsang et-al., 1972;Ichii, 1972;Albano et al, 1974) or by (NH4)2SO4 precipitation (Rabinowitz & Katz, 1973). The standard curve for this assay by (NHF)2SO4 precipitation was plotted in the conventional manner ( Fig.…”
Section: Characteristics Of Cyclic (3h]amp Binding By Adrenal-cortex mentioning
confidence: 99%
“…The cyclic AMP-dependent protein kinases have subunits whose specificity and high affinity for cyclic AMP make these enzymes useful as binding reagents in competitive-binding assays for this nucleotide. The binding reagent is minimally purified tissue extracts (Brown et al, 1971;Ichii, 1972;Tsang et al, 1972;Rabinowitz & Katz, 1973;Cooper et al, 1972), the isoenzyme form of protein kinase eluted from DEAE-cellulose at low ionic strength (Brostrom & Kon, 1974;Tovey et al, 1974) or the protein kinase isoenzyme eluted at higher ionic strength (Gilman, 1970;Walton & Garren, 1970;Sanborn etal., 1973). Bound and free isotope is most often separated by membrane filtration (Gilman, 1970;Walton & Garren, 1970;Ichii, 1972;Sanborn et al, 1973;Gilman & Murad, 1974;Gill & Walton, 1974) or dextran-coated charcoal (Brown et al, 1971;Tovey et al, 1974).…”
mentioning
confidence: 99%